Педагогічні умови формування готовності до відтворення народного стилю одягу - Кокаш Ержейбет; Kokash Erzheybet; Kokas Erzsébet (Видавництво «Код», 2024)
Резюме. У статті в результаті проведеного дослідження уточнено зміст дефініцій «умови», «педагогічні умови», схарактеризовано стиль українського вбрання. У процесі проведення пошукової роботи ми визначили педагогічні умови формування готовності до вивчення і відтворення особливостей народного стилю одягу Великодобронської громади Закарпатської області, а саме: стимулювання мотивації до розвитку творчого потенціалу особистості у створенні народного стилю одягу; створення народного стилю одягу визначаємо в сегменті використання інтерактивних форм і методів художньо-творчої діяльності з метою актуалізації потреби в самовдосконаленні й розвитку особистісних якостей; активізація самостійної роботи з використанням особистісно зорієнтованої взаємодії з оточуючим середовищем, яка базується на розкритті індивідуальних якостей суб’єктів діяльності. У процесі дослідницької діяльності доведено, що запровадження педагогічних умов формування готовності до відтворення народного стилю одягу передбачає використання наступних підходів: системного, компетентнісного, особистісно зорієнтованого, праксеологічного, необхідних умінь і навичок раціональної творчої діяльності, культурологічного, аксіологічного, технологічного.

Abstract. Thus, as a result of the conducted research, we clarified the content of the definitions of «conditions», «pedagogical conditions», and characterized the style of Ukrainian clothing. In the process of conducting search work, we determined the pedagogical conditions for the formation of readiness to study the peculiarities of the folklore style of clothing of the Veliko Dobron community of Zakarpattia region, namely: stimulation of motivation for the development of the creative potential of the individual in the creation of the folklore style of clothing; we define the creation of a folk style of clothing in the segment of the use of interactive forms and methods of artistic and creative activity in order to actualize the need for self-improvement and development of personal qualities; activation of independent work using personal-oriented interaction with the environment, which is based on the disclosure of individual qualities of the subjects of activity. In the process of research, it has been proven that the introduction of pedagogical conditions for the formation of readiness to study folklore style of clothing involves the use of the following approaches: systemic, competence-oriented, personally oriented, praxeological, necessary abilities and skills of rational creative activity, cultural, axiological, technological. It has been proven that clothing style is one of the main elements of every person’s image. Certain substyles are distinguished within one style. A person’s image is influenced by accessories, color of clothes, selection of fabrics, details of individual models of clothes, shoes. Currently, a person’s clothing style is determined by gender, age, social status and profession. The style of clothing is influenced by a person’s personal taste, environment, religious affiliation, lifestyle and individual and ethnic characteristics of each person.
Pedagogical conditions for the formation of readiness to recreation of the national style of clothing
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014095 https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-8
Keywords: педагогічні умови; народний стиль одягу; художньо-творча діяльність